f + s + t = 84 (1)

s = 3t (2)

t = f + 6 (3)

substitute for s in (1)

f + 4t = 84 (4)

substitute for t in (4)

f + 4(f + 6) = 84

simplify

5f + 24 = 84

__f = 12__

sub for f in (3)

__t = 18__

sub for t in (2)

__s = 54__

Check

f + s + t = 84 - answer is correct.

f + s + t = 84 (1)

s = 3t (2)

t = f + 6 (3)

substitute for s in (1)

f + 4t = 84 (4)

substitute for t in (4)

f + 4(f + 6) = 84

simplify

5f + 24 = 84

__f = 12__

sub for f in (3)

__t = 18__

sub for t in (2)

__s = 54__

Check

f + s + t = 84 - answer is correct.

Didn't find the answer you were looking for?